An investigation of the molecular complexities that regulate molting in decapod crustaceans - Pitts, Natalie Lynn, author; Mykles, Donald L., advisor; Garrity, Deborah M., committee member; Tjalkens, Ronald B., committee member; Tsunoda, Susan, committee member (Colorado State University. Libraries, 2015)
Molting in decapod crustaceans is regulated by the interaction of two hormones, molt inhibiting hormone (MIH) and ecdysteroids. Ecdysteroids are steroid hormones secreted from the molting gland or Y-organ (YO) and fluctuations in hemolymph ecdysteroid titers regulate progression through the molt cycle. Secretion of ecdysteroids is controlled by the peptide hormone MIH, which is synthesized and released from the X-organ/sinus gland (XO/SG) complex in the eyestalk ganglia (ESG). The field of crustacean endocrinology has mainly focused on understanding the molecular underpinnings of MIH’s action on ecdysteroid production in the YO. The goal of this dissertation was to examine how MIH synthesis and secretion from the XO/SG complex contributes to molt cycle progression. Blackback land crabs, Gecarcinus lateralis, were induced to molt via autotomy of five or more walking legs (multiple limb autotomy or MLA). ESG were collected from intermolt, premolt, and post-molt animals and changes in expression of Gl-MIH and mTOR signaling pathway components were investigated. There was a significant effect of molt stage on Gl-MIH and mTOR signaling pathway gene expression in the ESG of G. lateralis. Continuous elevation of MIH transcript abundance during pre and post molt indicates that MIH titers in the hemolymph are not regulated by changes in transcript abundance. Molting also significantly increased expression of Gl-Akt, Gl-mTOR, Gl-Rheb, and Gl-S6K in one or more molt stages. Akt inhibits the tuberous sclerosis complex allowing for the activation of Rheb. Rheb is a GTPase that binds and activates the mechanistic target of rapamycin (mTOR). mTOR activates S6 kinase (S6K), increasing protein synthesis. ESG of naturally molting green crabs, Carcinus maenas, were also collected from intermolt, early premolt, and post molt animals. Molting had little effect on gene expression in C. maenas, confirming previous findings that molt progression is regulated post transcriptionally. This dissertation identifies a novel nitric oxide (NO) binding protein in the SG of C. maenas. The hypothesis is that NO negatively regulates MIH secretion from the SG thereby controlling molt progression. This unidentified endogenous binding protein allows NO to be present in the SG for a prolonged period and can therefore continually regulate neuropeptide release. Localization of the enzyme that produces NO (nitric oxide synthase; NOS) and MIH in the SG of C. maenas, G. lateralis, and Metacarcinus magister is consistent with the hypothesis that NO is a regulator of neuropeptide release in the crustacean SG. The second goal of this dissertation was to explore why some crustacean populations or individuals within a population are refractory to molt induction. The Bodega Bay population of C. maenas is refractory to molt induction techniques and a similar phenomenon is observed in G. lateralis. Some G. lateralis induced to molt via MLA did not enter premolt 90 days post induction and were classified as "blocked." These animals underwent a second molt induction technique, eyestalk ablation (ESA), and YO, brain (Br), and thoracic ganglia (TG) were collected at 1, 3, and 7 days post ESA. Gene expression of MIH and mTOR signaling pathway genes was examined in all three tissues (see Figure 3 for MIH signaling pathway components and there interactions). Results from this experiment suggested that a similar mechanism of molt resistance exists between C. maenas and G. lateralis. ESA did not increase hemolymph ecdysteroid titers of blocked animals, whereas ESA significantly increased ecdysteroid titers in control and intermolt animals. Gl-MIH expression in the ESG and expression of many Gl-MIH signaling components in the YO were upregulated in blocked animals, suggesting that the blocked animals were in a "hyper-repressed" state, and therefore resistant to molt induction by ESA and MLA. In both species, MIH is expressed in the Br and TG. The hypothesis is that MIH secretion from these other central nervous system (CNS) tissues contributes to a resistance to molt induction techniques. Expression of MIH signaling pathway genes is unchanged in the Br and TG in response to ESA. These data suggest that MIH does not activate a signaling pathways in CNS tissues but like the ESG, MIH is synthesized and secreted from these tissues. This experiment also supports the growing body of literature that mTOR inhibition activates downstream transcription factors which are important in maintaining energy homeostasis in times of environmental stress.
Keywords: crustaceans; immunofluorescence; molt inhibiting hormone; molt regulation; nitric oxide; quantitative PCR